Polanyi contre Freeman - Nicolas Postel; Richard Sobel (Revue de la Régulation, 2011)
The dominant approach of CSR is based on the concept of “stakeholders” (R. E. Freeman). More than a theory, it is a slogan which irrigates as much the scientific discourse as the manager and political discourses. We can make two readings of this slogan. The first one, which is very reducing for us, consists on the deconstruction of the firm as institution and its replacement by a market representation based on bilateral exchanges between rational individuals. The second one, more promising in order to identify the potentialities of CSR in terms of regulation, intends to found the notion of stakeholder on a theory of actor and institution. It is the position which we defend by mobilizing Karl Polanyi’s institutionnalism.